ANALISIS PENYALURAN BANTUAN SOSIAL PADA MASA PEMILU PERSPEKTIF SILA KEADILAN SOSIAL BAGI SELURUH RAKYAT INDONESIA - Sri Hartati; SRI SETIAWATI; Rubiyanto Rubiyanto (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2025)
The social assistance program (Bansos) has become the main instrument in the government's performance to alleviate poverty and ensure community welfare. However, the phenomenon of misuse of social assistance for political purposes, especially in the context of general election campaigns (Pemilu), is an issue that raises serious concerns in realizing the principles of justice, transparency, and accountability in realizing elections that are